Monte Carlo modelling of hole transport in MDMO-PPV: PCBM blends - Choulis, Stelios A.; Chatten, Amanda J.; Tuladhar, Sachetan M. (My University, 2005)
We propose a model of hole transport in interpenetrating two-phase systems and apply it to blends of poly[2-methoxy-5-3(3′,7′-dimethyloctyloxy) -1-4-phenylene vinylene], (MDMO-PPV), and 1-(3-methoxycarbonyl)-propyl-1-phenyl- (6,6)C 61, (PCBM) with low PCBM content. The main features of the model are that hole transport is mediated by a small polaron tunnelling expression and that the density of states contains a tail of deep traps, which serve to delay carrier transport. The exponential factor governing the depth of these localised states is derived from transient optical measurements. The model is implemented using Monte Carlo simulations and is applied to reproduce both the time of flight hole photocurrent transients and the field dependence of the hole mobilities extracted from the data. We show that the transport behaviour detected by time of flight and transient absorption spectroscopy can be described quantitatively with a single transport model
Keywords: Absorption spectroscopy; Polychlorinated biphenyls